2017
DOI: 10.3390/su9101700
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Urban Climate Landscape Patterns on Land Surface Temperature in Wuhan, China

Abstract: Facing urban warming, mitigation and adaptation strategies are not efficient enough to tackle excessive urban heat, especially at the local scale. The local climate zone (LCZ) classification scheme is employed to examine the diversity and complexity of the climate response within a city. This study suggests that zonal practice could be an efficient way to bridge the knowledge gap between climate research and urban planning. Urban surfaces classified by LCZ are designated as urban climate landscapes, which exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 42 publications
4
21
0
Order By: Relevance
“…LCZ G (Water) displayed high-night time temperature because of its high specific capacity, which result to a slower release of heat at night The lowest night-time mean temperature (visualized as blue in The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, Volume XLII-4/W19, 2019 PhilGEOS x GeoAdvances 2019, 14-15 November 2019, Manila, Philippines night-time LST in Figure 10) was identified in LCZ A (Dense trees) and LCZ F (Bare soil or sand). The variations in daytime and night-time LST (Figure 11) showed consistency with profiles from other literature (Yang et al, 2017;Wang et al, 2017;Cai et al, 2018). Earth's surface absorbs heat during the day and radiates it back at night.…”
Section: Lcz Map Of Quezon Citysupporting
confidence: 87%
“…LCZ G (Water) displayed high-night time temperature because of its high specific capacity, which result to a slower release of heat at night The lowest night-time mean temperature (visualized as blue in The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, Volume XLII-4/W19, 2019 PhilGEOS x GeoAdvances 2019, 14-15 November 2019, Manila, Philippines night-time LST in Figure 10) was identified in LCZ A (Dense trees) and LCZ F (Bare soil or sand). The variations in daytime and night-time LST (Figure 11) showed consistency with profiles from other literature (Yang et al, 2017;Wang et al, 2017;Cai et al, 2018). Earth's surface absorbs heat during the day and radiates it back at night.…”
Section: Lcz Map Of Quezon Citysupporting
confidence: 87%
“…In addition, the appropriate scale also depends on landscape matrix selection. For instance, the SHDI showed the strongest correlation with LST at the 700 m scale which was not the optimal solution if other landscape matrices were taken into account, as indicated by a case study of Wuhan, China [53]. In this sense, further research is warranted to examine the scale sensitivity of their relationships in the future to lead to more comprehensive understanding.…”
Section: Which Underlying Properties Are Significantly Related To Thementioning
confidence: 99%
“…Referring to previous studies [40,[64][65][66], a matching with tolerable multicollinearity (VIF < 10) was identified as the final indicator system for later modeling in this study. All variables are resampled to the city block scale of 500 m in urban climatology research [70], as identified by multiple related studies to be the optimal spatial scale for exploring LST and landscape association in Wuhan [27,71]. The city block scale is also recommendable for city-scale study as it is the smallest urban unit where homogeneity is possible while also large enough to generate localized breeze systems [70].…”
Section: The Selection and Retrieval Of Landscape Indicatorsmentioning
confidence: 99%